The Effect of Intrauterine Exposure of Antibiotics on The Risk of Atopic Dermatitis in Asian Children: A Systematic Review - Husna, Rosalia Soraya (CV. Publikasi Indonesia, 2025)
Introduction: Atopic dermatitis (AD) is a chronic inflammatory skin condition characterized by pruritus and recurrent skin lesions, affecting a significant percentage of children globally. The prevalence of AD is rising, particularly in Asian populations, potentially due to rapid urbanization and environmental changes. This systematic review explores the impact of intrauterine antibiotic exposure on the risk of developing AD in Asian children, considering the multifactorial nature of the disease influenced by genetic and environmental factors. Objectives: The primary objective of this review is to synthesize existing research on the correlation between maternal antibiotic exposure during pregnancy and the incidence of AD in offspring within Asian populations. The review aims to identify potential modifiable risk factors and elucidate the underlying mechanisms contributing to AD development. Methods: The review adhered to the 2020 PRISMA guidelines, conducting a comprehensive literature search using PubMed and Cochrane Library. The search strategy focused on studies published in English between 2000 and 2025, involving keywords related to antibiotics, maternal exposure, and atopic dermatitis. Inclusion criteria encompassed studies with healthy mothers and accessible full texts, while exclusion criteria involved studies lacking essential details. Results: The review included 6 prospective cohort studies from China, Japan, South Korea, and Taiwan, with a total sample sizes of 1.073.245 mother-children pairs ranging from 412 to 900,584 participants. The studies employed various methods to assess antibiotic exposure, including maternal urine samples, parent-reported data, and medical records. Results varied, with some studies indicating a significant correlation between antibiotic exposure and increased AD risk, while others found no association. The inconsistency in findings highlights the complexity of AD and the influence of genetic and environmental factors. Discussion: The findings suggest a multifaceted relationship between maternal antibiotic exposure and AD risk, potentially mediated by alterations in gut microbiota and immune system development. The variability in results underscores the need for standardized methodologies and further research to clarify the mechanisms involved. The review emphasizes the importance of considering genetic predisposition and environmental influences in understanding AD etiology. Conclusion: This systematic review indicates a possible link between prenatal antibiotic exposure and AD in Asian children, though evidence remains inconclusive. Further research is necessary to elucidate the underlying mechanisms and identify modifiable risk factors. Understanding the impact of antibiotics on AD progression could inform clinical practices and public health strategies, potentially leading to targeted interventions to reduce AD prevalence in high-risk populations.